Quel régime politique pour les états Africains : le cas du Togo - Koupokpa, Elisée Tikonimbé (Afrika Focus, 2014)
As it is the case for most of the African countries, Togo is looking for a constitutional system that ts its political, social and cultural realities. The 1990s were considered as a period of democratic revival, and from those years onwards the constitutional organization was directed towards a parliamentary type of regime which was rightfully or wrongfully seen as an instrument whereby the head of state's powers were limited. However, the unfortunate result of this kinds of organization of the political powers leads to another constitutional system which is more likely to be presidential. Key words: political regime, parliamentary Regime, presidential regime, head of state, president of the republic, prime minister, counterbalance